Sociology of Markets: Excursion to the New Methodology. Critical Review on the book by Vadim Radaev “Sociology of markets: towards formation of the new approach” - Максим Анатольевич Сторчевой (Journal of Economic Sociology, 2010)
Detailed description in the text